Implementasi Good Governance dalam Mendorong Pencapaian SDGs melalui Pemanfaatan Dana Desa: Studi Kasus Desa Janti, Waru, Sidoarjo - Della Erdiana; Muhammad Taufiq Hidayat (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the implementation of good governance in encouraging the achievement of Sustainable Development Goals (SDGs) through Village Fund utilization in Janti Village, Waru District, Sidoarjo Regency. A descriptive qualitative approach was employed, using in-depth interviews, direct observation, and document analysis of RPJMDes, RKPDes, APBDes, and accountability reports. The findings indicate that village fund management has complied with regulatory procedures and applied core principles of good governance, particularly transparency, accountability, and community participation. These practices have contributed to the achievement of several SDGs indicators, including poverty reduction, improved public health, quality education, gender equality, economic growth, infrastructure development, environmental resilience, and institutional strengthening at the village level. However, the overall achievement of SDGs Village remains suboptimal due to limited human resource capacity, insufficient technical understanding of SDGs indicators, and budgetary constraints. This study concludes that while good governance provides a strong institutional foundation, the effectiveness of SDGs achievement depends on the availability of competent human resources, adequate funding, and strategic prioritization aligned with SDGs indicators. Strengthening village capacity and targeted policy support are therefore essential to ensure sustainable and inclusive rural development.